Induced antibodies directed to the angiotensin receptor type 1 provoke skin and lung inflammation, dermal fibrosis and act species overarching. Issue 9 (20th May 2022) - Yue, Xiaoyang; Yin, Junping; Wang, Xiaoqing; Heidecke, Harald; Hackel, Alexander Maximilian; Dong, Xiaoru; Kasper, Brigitte; Wen, Lifang; Zhang, Liang; Schulze-Forster, Kai; Junker, Juliane; Grasshoff, Hanna; et al.
Abstract : Objective: To determine contributions and functions of autoantibodies (Abs) directed to the angiotensin receptor type 1 (AT1R), which are suggested to be involved in the pathogenesis of AT1R Abs-related diseases such as systemic sclerosis (SSc). Methods: C57BL/6J mice were immunised with membrane-embedded human AT1R or empty membrane as control. Mice deficient for CD4 + or CD8 + T cells and B cells were immunised with membrane-embedded AT1R or an AT1R peptide proposed to be a dominant T cell epitope. A monoclonal (m)AT1R Ab was generated by hybridoma technique and transferred into C57BL/6J and AT1Ra/b knockout mice. The induced phenotype was examined by histology, immunohistochemistry, immunofluorescence, apoptosis assay and ELISA. In vitro, Abs responses towards AT1R were measured in cells of different origins and species. Results: AT1R-immunised mice developed perivascular skin and lung inflammation, lymphocytic alveolitis, weak lung endothelial apoptosis and skin fibrosis accompanied by Smad2/3 signalling, not present in controls or mice deficient for CD4 + T and B cells. The AT1R peptide 149–172 provoked lung inflammation. Application of the mAT1R Ab induced skin and lung inflammation, not observed in AT1Ra/b knockout mice. In vitro, AT1R Abs activated rat cardiomyocytes and human monocytes, enhanced angiotensin II-mediated AT1R activation in AT1R-transfected HEK293 cells via AT1R binding and mAT1R Ab-activated monocytes mediated the induction of profibrotic markers in dermal fibroblasts. Conclusion: Our immunisation strategy successfully induced AT1R Abs, contributing to inflammation and, possibly, to fibrosis via activation of AT1R. Therefore, AT1R Abs are valuable targets for future therapies of SSc and other AT1R Ab-related diseases.